Dermatoglyphic Patterns Among Adolescents of the Ebira Ethnic Group of Kogi State, Nigeria - Yusuf, Abdullateef Onoruoiza; Danborno, Barnabas; Timbuak, James Abrak (Journal of Morphological Sciences, 2019)
Dermatoglyphics have been widely studied and have been shown to vary across different ethnic populations. The present study investigates the dermatoglyphic patterns among adolescents of the Ebira ethnic group through selected dialects. A total of 591 subjects, both males and females, participated in the study. Prints were collected by conventional ink and roller method and read using hand magnifying lens. Analyses were performed using descriptive statistics, analysis of variance (ANOVA), t-test, and the chi-squared test. P-values < 0.05 were considered statistically significant. The result of the study showed that the three dialects had similar distribution of fingerprint patterns in the order ulnar loop > whorl > arch > radial loop. The fingerprint pattern showed strong statistical association with gender both within and across the dialects (p < 0.001). The palmar crease of the subjects showed the normal palmar crease to be the most prevalent (87%), followed by the Sidney crease (9%), and the Suwon crease (4%) being the least prevalent for both palms across the dialects. There was strong association with palm crease type and gender, with p < 0.001. The triradii angles of the palms revealed a mean value of acute angles. Females had significantly higher mean atd angles compared with male subjects, while males had significant higher mean dat angles compared with females for the three dialects. The adt angle, however, showed no significant mean difference between males and females. In conclusion, the present study evaluated the fingerprint patterns, the palmar creases and the triradii angles conforming anthropological similarities within these three dialects. However, gender differences were observed for the three dialects, with Ebira-Tao and Ebira-Etuno exhibiting shared patterns.
Keywords: dermatoglyphics; Ebira; fingerprints; palmar; triradii